Reducing Rural Fire Risk through the Development of a Sustainable Supply Chain Model for Residual Agroforestry Biomass Supported in aWeb Platform: A Case Study in Portugal Central Region with the Project BioAgroFloRes - Casau, Margarida (2022)
In the European Mediterranean region, rural fires are a widely known problem that cause serious socio-economic losses and undesirable environmental consequences, including the loss of lives, infrastructures, cultural heritage, and ecosystem services such as carbon sequestration and the provisioning of raw materials. In the last decades, the collapse of the traditional rural socioeconomic systems that once characterized the Mediterranean region, along with land-use changes, have created conflicts and additional driving factors for rural fires. Within Europe, Portugal is the most affected country by rural fires. This work intends to demonstrate the importance of recovering and valorizing residual agroforestry biomass to reduce rural fire risk in Portugal, and thus contributing to a fire resilient landscape. From the results of the known causes of fires in Portugal, it becomes very clear that it is crucial to educate people to end risky behaviors, such as the burning of agroforestry leftovers that causes 27% of fires in Portugal each year. The valorization of the existing energy potential in the lignocellulosic biomass of agroforestry residues favors the reduction of the probability of rural fires, this being the focus of the project BioAgroFloRes—Sustainable Supply Chain Model for Residual Agroforestry Biomass supported in a Web Platform—introduced and explained here